Boosting performances of triboelectric nanogenerators by optimizing dielectric properties and thickness of electrification layer. Issue 30 (6th May 2020) - Kang, Xiaofang; Pan, Chongxiang; Chen, Yanghui; Pu, Xiong
Abstract : Enhanced output performances of a triboelectric nanogenerator (TENG) are achieved by optimizing the high-dielectric-constant filler content in the electrification layer and decreasing its thickness. Abstract : Triboelectric nanogenerators (TENGs) with excellent flexibility and high outputs are promising for powering wearable/wireless electronics with electricity converted from ubiquitous mechanical energies in the working environment. In this work, the effects of the dielectric properties and thickness of the electrification film on the performance of the TENG are discussed. BaTiO3 nanoparticles are added into poly(vinylidene fluoride) (PVDF) to improve the dielectric constant of the composite film. The TENG using a BaTiO3 /PVDF nanocomposite film with 11.25 vol% BaTiO3 as the tribo-negative electrification layer is demonstrated to be the optimized one, and generates an open-circuit voltage of 131 V and transferred short-circuit charge density of 89 μC m −2, 6.5 fold higher than those of a TENG using bare a PVDF layer. Furthermore, by reducing the thickness of the BaTiO3 /PVDF film to 5 μm, the voltage and charge density increase to 161 V and 112 μC m −2, respectively, and an instantaneous peak power density of 225.6 mW m −2 is obtained.